Investing in adaptation: Flood risk and real option application to Bilbao. (September 2017) - Abadie, Luis Maria; Sainz de Murieta, Elisa; Galarraga, Ibon
Abstract: Investment decisions in adaptation are usually made under significant uncertainty due to climate change and socio-economic trends. In this study, we propose three ways to incorporate climate and socio-economic uncertainty into the assessment of an adaptation infrastructure designed to cope with flood-risk in the city of Bilbao. First, we use stochastic modelling to estimate the present value of expected damage over a time period, considering that extreme events may increase in the future. Second, we develop an additional calculation that incorporates two risk measures used in financial economics: Value-at-Risk and Expected Shortfall, the latter being a less common but better risk indicator. Third, we illustrate a case of Real Options Analysis (ROA) in which a binomial tree is used to study whether the best decision at present is to invest now or to delay the investment decision. Highlights: Decision making under uncertainty is a critical issue when addressing adaptation. We present three ways to incorporate uncertainty into adaptation investments. Stochastic modelling is developed to estimate expected damages over time. Risk measures focus on the impact of low probability, high damage events. The Real Options Analysis (ROA) allows quantifying the investment risk.